2022
DOI: 10.3390/biomedicines10112676
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Association between Gut and Urine Microbiota and Prostatic Disease including Benign Prostatic Hyperplasia and Prostate Cancer Using 16S rRNA Sequencing

Abstract: Numerous microorganisms residing in the gastrointestinal and genitourinary tracts affect host health. We investigated stool and voided urine samples collected from patients with benign prostatic hyperplasia (BPH) or prostate cancer (PC) and a control group to explore the potential relationship between human microbiota and prostatic disease, and aimed to identify correlations and pathogenic taxonomic units. We studied microbial composition using 16S rRNA sequencing to identify operational taxonomic units (OTUs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Another study reported that the intake of fermented milk containing L. casei increased the activity of natural killer cells [ 23 ], and Lactobacillus inhibited human prostate cancer cell tumor necrosis factor related apoptosis-inducing ligand (TRAIL) [ 24 ]. However, another study reported conflicting findings that the abundance of Lactobacillus in the urine was increased in patients with BPH and prostate cancer [ 25 ]. In this study, the induction of BPH using testosterone undecanoate significantly reduced the abundance of Lactobacillus compared with that in the normal control group and consistently decreased the abundances of Bacilli, Lactobacillaceae, and Lactobacillales, to which Lactobacillus belongs.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the intake of fermented milk containing L. casei increased the activity of natural killer cells [ 23 ], and Lactobacillus inhibited human prostate cancer cell tumor necrosis factor related apoptosis-inducing ligand (TRAIL) [ 24 ]. However, another study reported conflicting findings that the abundance of Lactobacillus in the urine was increased in patients with BPH and prostate cancer [ 25 ]. In this study, the induction of BPH using testosterone undecanoate significantly reduced the abundance of Lactobacillus compared with that in the normal control group and consistently decreased the abundances of Bacilli, Lactobacillaceae, and Lactobacillales, to which Lactobacillus belongs.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of An (54), BPH induction altered the abundance of Flavonifractor, and Flavonifractor coule be a potential indicator for the diagnosis of BPH. Although there are limited studies investigating other gut microbiota and prostate or androgen levels, these gut microbiota are mostly found in the correlation of colorectal cancer metabolism, immune function and anti-in ammation (15). Further studies on these gut microbiota are highly needed.…”
Section: Discussionmentioning
confidence: 99%
“…In Du's study, an experimental autoimmune prostatitis mouse model was developed to investigate whether gut micro ora modulates Th17/Treg Cell differentiation via the short-chain fatty acid propionate, which may represent the pathogenic function of gut microbiota in prostatitis (13). More and more studies show that the gut microbiota of men with and without prostate cancer differs signi cantly (14)(15)(16)(17). Pathways in folate and arginine metabolism were shown to be elevated in PCa patients using gene-based functional analysis of intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who were pregnant, menstruating, diagnosed with malignant tumors, autoimmune diseases, urethritis, prostatitis, benign prostatic hyperplasia ( Tsai et al, 2022 ), renal cysts, bladder inflammation, urinary tract abnormalities, had undergone urinary catheterization within the past 4 weeks, or had used antibiotics or probiotic products within the past 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected as previously described in Tsai et al (2022) . Specifically, the bacterial DNA isolation, 16 S rRNA sequencing, and bioinformatics ( Liu et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%